'Different than us'? Reciprocal perceptions of the societies in Turkey and North Cyprus. Issue 3 (27th May 2022) - Ergul Jorgensen, F. Asli; Latİf, Dilek
ABSTRACT: This study explores the reciprocal perceptions, main tendencies, prejudices and expectations of the societies in Turkey and North Cyprus. To this end, 160 participants from both societies were interviewed. The specific social processes that result in various judgements, thoughts and tendencies observed in the semi-structured interviews were evaluated by the discourse analysis method. Although the research findings and analyses are not representative of the whole populations, they still shed light on common perceptions. In fact, the results counterintuitively revealed that people from both societies exhibit increasing suspicion, if not negativity, about each other despite the widely accepted nationalist narrative of 'motherland-babyland', which is believed to be the main dynamic of the relations.